Pb Dan Cu Pada Badan Air Dan Tanah Sawah Sub-Das Solo Hilir Kabupaten Lamongan - W Purbalisa; Mulyadi Mulyadi (Faculty of Agriculture, Pattimura University, 2013)
The main components of the watershed which are potentially contaminated, are bodies of water and soil. Deterioration of water quality in the watershed, among others, is caused by industrial waste water disposal systems and household waste along the river resulting pollution. Lamongan district is located at sub watershed of Solo river downstream. Data distribution of Pb and Cu in water and paddy soil of sub watershed Solo downstream was limited, therefore this research was done. The research was conducted in 2009. The aim of the research was to get data distribution of heavy metal Pb and Cu in paddy soil and water watershed Solo downstream Lamongan district. Soil samples were taken with a modified grid system, by collecting a composite soil samples representing of area about 10-15 ha, while the water samples taken at a depth of 25-30 cm of water surface. The result showed the water quality of the river from 9 sampling sites, there were 7 location of BOD value already exceeding the maximum value for agriculture water. While the COD value and electrical conductivity at 1 and 3 locations respectively already exceeded the maximum. Cu was detected at all sampling sites, while Pb was detected only in 5 locations. Pb and Cu levels was below the maximum limit specified in PP No. 21, 2001. Cu in soils was detected at all sites, while there were 4 locations that Pb was not detectable, levels of Pb and Cu in soils were still under the specified threshold.